(untitled) (Research, Society and Development, 2020)
The study aimed to analyze the eating pattern during the period of social distance as well as the anxiety caused by this new scenario. For data collection, a questionnaire with sociodemographic data was applied; symptoms; contact history with COVID-19; changes in eating habits and physical activity; food consumption; and anxiety symptoms. The sample consisted of 1000 questionnaires, the majority (54.7%) are eutrophic and anxious (84%). Regarding eating habits, 79.1% stated changes in consumption and preparation of meals. Daily food consumption of healthy foods was higher for whole foods, fruits and beans. In addition, there was a statistical difference in the relationship between anxiety and food consumption, with anxious people who consumed the most unhealthy foods. Although the level of anxiety in the sample was worrying, isolation made it possible to prepare and carry out meals at home, increasing the consumption of healthy foods.